Manilkara dardanoi (Sapotaceae): the rediscovery of an endemic and threatened species in northeastern Brazil - Jr., Eduardo Bezerra De Almeida; Zickel, Carmen Silvia (Phytotaxa, 2014)
The present study reports the rediscovery of Manilkara dardanoi in the Atlantic Forest, which complements the original description of this species. As the only previous reports of M. dardanoi date from 1950 and 1952, excursions were made to various municipalities in Pernambuco, and collections housed in Brazilian herbaria were consulted. The rediscovery of this species occurred in a secondary forest fragment in Pernambuco State. The species M. dardanoi is endemic to northeastern Brazil, and its rediscovery demonstrates the value of intensive collection during floristic studies, with four samples collected.